An ultra-low-dose protocol for computed tomography-guided lung radiofrequency ablations. (1st December 2022) - Golin, Melissa; Izaaryene, Jean; Dassa, Michael; Piana, Gilles; Ferre, Marjorie
Abstract: To evaluate the safety and efficacy of ultra-low-dose (ULD) protocol for computed tomography (CT)-guided lung radiofrequency ablation (RFA). Patients who had undergone lung RFA between November 2017 and January 2021 were consecutively and retrospectively included. Thirty patients were treated using a conventional standard protocol (SP), including helical acquisitions with mA automatic adjustment and sequential CT at 80 kVp; and 31, with a ULD protocol defined with helical acquisitions with fixed mA and sequential series at 100 kVp. These parameters were selected from those used for a diagnostic lung low-dose CT scanner. Patient characteristics, dose indicators, technical efficacy (minimal margin [MM], recurrence during follow-up), and complications (pneumothorax, alveolar haemorrhage, and haemoptysis) were recorded. We included 61 patients (median age, 65 [54–73] and 33 women), with no significant differences according to the type of protocol, except for the type of anaesthesia. Even if the number of helical acquisitions did not significantly change, all dose indicators significantly decreased by 1.5-fold–3-fold. The median dose-length-product and effective dose, with their ranges, respectively, were 465 mGy cm (315–554) and 6.5 mSv (4.4–7.8) in the SP group versus 178 mGy cm (154–267) and 2.5 mSv (2.2–3.7) in the ULD group, ( p < 001). The ULD group exhibited lower intraoperator variability and better interoperator alignment than those of the SP group. The MM was not significantly different between the two groups (4.6 mm versus 5 mm, p = 16). One local recurrence was observed in each group at 8 months in the SP and at one year in the ULD group ( p = 1). The complication rates did not differ significantly. Implementing an ULD protocol during lung RFA may provide similar efficacy, a reduction of dose indicators, and intra- and interoperator variability, without increasing complication rates, compared to those associated with an SP.